Teaching the Bible at public universities in South Africa: A proposal for multidisciplinary approach - Dube, Zorodzai (HTS teologiese studies, 2013)
How should the academy teach the Bible? I noted two challenges to this endeavour. Firstly, the Bible has been used as superstructure to justify and to solidify colonialism and apartheid in South Africa which resulted in people to mistrust the way the Western missionaries interpreted the Bible. It also gave birth to the inception of African Independent Churches (AIC) and an urgent need to reinterpret the Bible from the experiences of Africans. However, the initial question remains how the academy should teach the Bible. The complexity of this question is that despite the Bible’s association with a colonial legacy, the ordinary people did not stop reading the Bible and to make meaning of their lives from it. This study justifies the place of the Bible in public universities in South Africa and proposes ways the academy should teach the Bible. This study suggests a two-pronged approach to Biblical Studies at public universities. Firstly, the academy should critically engage the ideological presupposition underlying the theories used in the academy. Secondly, the academy must be open to the fact that the Bible is part of popular culture; hence, the academy should critically reflect how the Bible is used in public space. Therefore my hypothesis is that the academy should further focus on critiquing ideological inclinations that underline established truths in addition to focusing on the historical meaning of the Bible and establishing contextual similarities. Teaching the Bible should focus on analysing cultural, political and economic ideological truths that find support from the Bible. I propose that this line of thought is possible through cultural studies and/or interdisciplinary methods.